Pengaruh Perubahan Kebijakan Fiskal terhadap Perekonomian Indonesia: Perspektif Makroekonomi - Darsana, I Made; Sudjana, I Made (CV. Lafadz Jaya, 2024)
This study aims to analyze the impact of fiscal policy changes on Indonesia's economy from a macroeconomic perspective. Fiscal policy, which includes government expenditure and tax rates, significantly affects macroeconomic indicators such as economic growth (GDP), inflation, and unemployment. Using secondary data obtained from official sources such as Statistics Indonesia (BPS) and Bank Indonesia, the study applies regression analysis to examine the relationship between fiscal policy and Indonesia's economic performance. The findings show that expansionary fiscal policy can stimulate economic growth in the short term but poses risks of increasing inflation and national debt. Conversely, contractionary fiscal policy, although effective in controlling inflation and budget deficits, may slow down economic growth and increase unemployment if applied at the wrong time. Therefore, fiscal policy must be tailored to the prevailing economic conditions to achieve optimal results. This study contributes to understanding how fiscal policy impacts Indonesia's economy and emphasizes the importance of careful planning in implementing sustainable fiscal policies.